2013
DOI: 10.1007/s10157-013-0926-1
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of factors predicting end-stage renal failure or death in patients with microscopic polyangiitis with mainly renal involvement

Abstract: Survival rates do not relate to ESRF in MPA patients with mainly renal involvement. Although patients with ESRF required regular hemodialysis, longer survival can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…In a Japanese study of MPA patients with renal involvement, the survival was 79.5% at 6 months and 71.1% at 12 months [19]. Similarly, in our cohort, the overall survival rate at 6 and 12 months were 83.9% and 78.2%, respectively.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In a Japanese study of MPA patients with renal involvement, the survival was 79.5% at 6 months and 71.1% at 12 months [19]. Similarly, in our cohort, the overall survival rate at 6 and 12 months were 83.9% and 78.2%, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…It was reported that mortality in MPA was significantly higher than in GPA and EGPA, mainly because MPA patients developed severe renal failure at the onset of the disease [6, 9]. Wang et al analysed 64 MPA patients with renal involvement showing that the deterioration of renal function is associated with mortality [14], while another report in Japan found that renal function is not associated with overall survival in MPA patients with renal involvement [19]. In this study, a serum creatinine level ≥500 μmol/L at diagnosis was an independent predictive factor for both mortality and ESRD, with hazard ratios of 2.207 and 8.236, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…112 A serum creatinine level above 4.6 mg/dL at initial MPA diagnosis was shown to be a good predictive factor for development of end stage renal failure, with 92.3% sensitivity and 84.6%specificity. 113 A recent study identified differential expression of genes associated with toll-like receptor signaling in peripheral neutrophils in MPA, however, evaluating the diagnostic potential of these patterns requires further research. 114 …”
Section: Anca Associated Vasculitides (Aav)mentioning
confidence: 99%
“…Another study also showed that the overall survival rates at 6 and 12 months after a diagnosis of MPA with renal involvement were 79.5% and 71.1%, respectively. Moreover, the severity of renal insufficiency was not related to the survival rate of patients with MPA with renal involvement (15).…”
mentioning
confidence: 94%